Ý định tiếp tục sử dụng ví điện tử của khách hàng Việt Nam và vai trò quan trọng của niềm tin - Hoàng Thị Phương, Thảo; Nguyễn Kim, Ngọc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
In connection with digitalization, e-wallets flourish in the Vietnamese e-payment market with a high volume of customers. However, the e-wallet providers have to tackle the intense competition with traditional banks and new players to gain market share. As a result, the best tactic for e-wallets providers is customer retention. The objective of this paper is to address the former concern by examining the antecedents of e-wallet customers’ continuance intention based on the Expectation Confirmation Model (ECM), Theory of Planned Behaviour (TPB), trust theory, and self-efficacy theory. The analysis result of 510 valid responses confirms the positive and direct effect of trust, satisfaction, perceived ease of use, perceived usefulness, self-efficacy, and social influence toward continuance intention. The moderating effect of trust on the relationship between satisfaction and continuance intention of Vietnamese customers is revealed.
Keywords: E-wallet; Customer trust; Usage continuance intention